2‐Deoxyglucose Dendrimer‐Enabled Niclosamide Delivery to FRβ‐Expressing Macrophages Alleviates Endometriosis Progression and Associated Hyperalgesia - Anubhav Dhull; Mingxin Shi; Madeleine E. Harvey; Taylor M. Page; Rishi Sharma; Kenneth John Goody; Aqib Iqbal Dar; Nash S. Moawad; Vijay Kumar Sirohi; Paul S. Cooke; Kanako Hayashi; Anjali Sharma (Advanced Healthcare Materials, 2026)
ABSTRACT Endometriosis (EuE) is a chronic, incurable disease. Due to limited efficacy, high recurrence rates, and serious side effects of current treatments, development of new, targeted, nonhormonal therapies is urgently needed. We previously reported that niclosamide, an FDA‐approved anthelmintic drug, attenuates endometriotic lesion growth. We further identified folate receptor‐β (FRβ)‐positive macrophages as contributors to disease progression. Significantly, niclosamide inhibits FRβ + macrophages and reduces inflammation, innervation, and angiogenesis. To develop niclosamide as a nonhormonal and selective immune cell‐targeted therapy for EuE, we engineered a folic acid (FA)‐conjugated 2‐deoxyglucose dendrimer (FA‐2DG‐D) using click chemistry to enable selective FRβ‐mediated uptake. Conjugation of niclosamide to FA‐2DG‐D yielded a targeted nanotherapeutic (FA‐2DG‐D‐Niclo) with enhanced aqueous solubility, controlled intracellular release, and excellent batch‐to‐batch reproducibility. In a mouse model of EuE, FA‐2DG‐D demonstrated lesion‐specific accumulation and selective internalization by FRβ + macrophages with minimal off‐target organ retention. A single intraperitoneal dose of FA‐2DG‐D‐Niclo (25 or 50 mg/kg/bw of niclosamide) significantly reduced FRβ + macrophage burden, suppressed lesion number and volume, and markedly improved EuE‐associated hyperalgesia at 2 weeks post‐treatment. Together, these findings establish FRβ + macrophages as a potential target in EuE and present FA‐2DG‐D‐Niclo as a nonhormonal, macrophage‐focused nanomedicine for precise and effective endometriosis treatment.